Small-fibre Neuropathy in Patients with Type 2 Diabetes Mellitus and its Relationship with Diabetic Itch: Preliminary Results - Aleksandra A. Stefaniak; Konstantin Agelopoulos; Dorota Bednarska-Chabowska; Grzegorz Mazur; Sonja Ständer; Jacek C. Szepietowski (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)